Effects of 2 or 5 consecutive exercise days on adipocyte area and lipid parameters in Wistar rats - Guerra, Ricardo L. F.; Prado, Wagner L.; Cheik, Nadia C.; Viana, Fabiana P.; Botero, Joao Paulo; Vendramini, Regina Célia [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Rossi, Elizeu Antonio [UNESP]; Damaso, Ana R. (Biomed Central Ltd., 2007)
Background: Exercise has been prescribed in the treatment and control of dyslipidemias and cholesterolemia, however, lipid responses to different training frequencies in hypercholesterolemic men have been inconsistent. We sought to verify if different frequencies of continuous moderate exercise (2 or 5 days/week, swimming) can, after 8 weeks, promote adaptations in adipocyte area and lipid parameters, as well as body weight and relative weight of tissues in normo and hypercholesterolemic adult male rats.Methods: Normal cholesterol chow diet or cholesterol-rich diet (1% cholesterol plus 0.25% cholic acid) were freely given during 8 weeks to the rats divided in 6 experimentals groups: sedentary normal cholesterol chow diet (C); sedentary cholesterol-rich diet (H); 5x per week continuous training normal cholesterol chow diet (TC5) and cholesterol-rich diet (TH5); 2x per week continuos traning normal cholesterol chow diet (TC2) and cholesterol-rich diet (TH2).Results: No changes were observed in lipid profile in normal cholesterol chow diet, but both 2 a 5 days/week exercise improved this profile in cholesterol-rich diet. Body weight gain was lower in exercised rats. Decrease in retroperitoneal and epididymal relative weights as well as reductions in adipocyte areas under all diets types were observed only in 5 days/week, while 2 days/week showed improvements mainly in cholesterol-rich diet rats.Conclusion: Our results confirm the importance of exercise protocols to control dyslipidemias and obesity in rats. The effects of 5 days/week exercise were more pronounced compared with those of 2 consecutive days/week training.